Evolution of Magnetic Field Fluctuations and Their Spectral Properties within the Heliosphere: Statistical Approach - Jana Šafránková; Zdeněk Němeček; František Němec; Daniel Verscharen; Timothy S. Horbury; Stuart D. Bale; Lubomír Přech (The Astrophysical Journal Letters, 2023)
We present the first comprehensive statistical study of the evolution of compressive and noncompressive magnetic field fluctuations in the inner heliosphere. Based on Parker Solar Probe (PSP) and Solar Orbiter data at various distances from the Sun, we show the general trends and compare them with Wind observations near 1 au. The paper analyzes solar wind power spectra of magnetic field fluctuations in the inertial and kinetic ranges of frequencies. We find a systematic steepening of the spectrum in the inertial range with the spectral index of around −3/2 at closest approach to the Sun toward −5/3 at larger distances (above 0.4 au), the spectrum of the field component perpendicular to the background field being steeper at all distances. In the kinetic range, the spectral indices increase with distance from −4.8 at closest PSP approach to ≈−3 at 0.4 au and this value remains approximately constant toward 1 au. We show that the radial profiles of spectral slopes, fluctuation amplitudes, spectral breaks, and their mutual relations undergo rapid changes near 0.4 au.